Urinary Tract and Other Associated Anomalies in Newborns With Esophageal Atresia - Eghbalian, Fatemeh; Monsef, Alireza; Mousavi-Bahar, Seyed Habibollah (Urology Journal, 2009)
Esophageal atresia is often associated with other anomalies. Hereditary and environmental factors may influence the incidence of associated anomalies, particularly of the urogenital system. We had 63 neonates with esophageal atresia admitted to 2 centers in Hamadan, Iran, from 2002 to 2008. They were 38 girls (60.3%) and 25 boy (39.7%). Tracheoesophageal fistula was present in 54 neonates (85.7%), and other associated anomalies in 10 (15.9%). Cardiac anomalies were found in 7 neonates; anorectal anomalies, in 4; urinary tract anomalies, in 2; and limb anomaly, in 1. Urinary tract anomalies (3.2%) were bilateral polycystic kidney in 1 neonate and unilateral hydronephrosis due to ureteropelvic junction obstruction in another. Both neonates with urinary tract anomalies were female and both had tracheoesophageal fistula, as well. Many of the associated congenital abnormalities influence the management protocol of esophageal atresia, and therefore, should be detected as soon as possible after birth.